2018
DOI: 10.1111/cod.13102
|View full text |Cite
|
Sign up to set email alerts
|

Adverse cutaneous reactions to skin care products on the face vary with age, but not with sex

Abstract: Our results indicate that pruritus, xerosis and erythema are common adverse cutaneous reactions to facial skin care products. These reactions vary with age, but not with sex. Vigorous safety testing should precede the marketing of skin care products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 33 publications
(59 reference statements)
3
9
0
1
Order By: Relevance
“…Correspondingly, we show here that skin care products were the number one factor associated with sensitive skin on the face of normal young Chinese. This finding parallels with recent observations that skin care products increasingly cause adverse cutaneous reactions . That more females than males proclaimed skin care products as trigger factor is likely linked to a higher prevalence of adverse cutaneous reactions to skin care products in females (Table ), possibly due to that more females than males used skin care products (24% vs 10%).…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, we show here that skin care products were the number one factor associated with sensitive skin on the face of normal young Chinese. This finding parallels with recent observations that skin care products increasingly cause adverse cutaneous reactions . That more females than males proclaimed skin care products as trigger factor is likely linked to a higher prevalence of adverse cutaneous reactions to skin care products in females (Table ), possibly due to that more females than males used skin care products (24% vs 10%).…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of ingredients can improve epidermal function. However, it is worth noting that a substantial portion of emollients on the market are harmful to epidermal function, although some ingredients in these products may benefit epidermal function [142][143][144][145]. The harmful emollients often contain some ingredient, such as eicosadienoic acid-enriched oils, stearic acid, ceteareth 20, PEG-40 castor oil and PEG-100 stearate, which all can induce cutaneous inflammation and/or disrupt epidermal permeability barrier [145][146][147][148].…”
Section: Natural Ingredientsmentioning
confidence: 99%
“…Thus, skin care product makers have been striving to develop products that can potently improve epidermal permeability barrier function. Because of the high incidence of adverse cutaneous reactions to skin care products, identification of safe and effective ingredients is becoming emergent [92, 93]. Our group has demonstrated that twice-daily applications of 2% hesperidin to young mouse skin for 6 days accelerated permeability barrier recovery in a model of acute barrier disruption although basal transepidermal water loss rates, stratum corneum hydration, and skin surface pH remained unchanged [31].…”
Section: Benefits Of Hesperidin For Cutaneous Functionsmentioning
confidence: 99%